Preparation of three dimensional flower-like cobalt phosphate as dual functional electrocatalyst for flavonoids sensing and supercapacitor applications. Issue 21 (1st November 2021) - Vinothkumar, Venkatachalam; Koventhan, Chelliah; Chen, Shen-Ming; Abinaya, Manickavasagan; Kesavan, Ganesh; Sengottuvelan, Nallathambi
Abstract: In this report, 3D flower-like cobalt phosphate (Co3 (PO4 )2, CPO) was prepared through a facile co-precipitation method towards voltammetric sensing of rutin (RU), quercetin (QCT) and also employed for supercapacitor application. The structural morphologies were analyzed by various analytical techniques. The Brunauer–Emmett–Teller analysis of CPO displays a specific surface area of 40.885 m 2 g −1 and a mesopore volume of 0.0108 cm 3 g −1, which provides more catalytic sites, and a good electron transfer pathway that leading to promote enhanced electrochemical performance for detection of RU, and QCT. The oxidation peak current demonstrated low detection limits of 0.009 μM for RU and 0.003 μM for QCT with broad linear concertation of RU and QCT were 0.02 → 121.62 μM, and 0.08 → 129.8 μM, respectively. The fabricated electrode shows a higher sensitivity of 1.352 and 3.847 μA μM −1 cm −2 for RU and QCT detection. The modified CPO/SPCE offers excellent selectivity, repeatability, reproducibility, and further monitoring for RU and QCT in spiked fruit samples showing applicable recoveries. The electrochemical supercapacitor was explored using a CPO/NF electrode that revealed high specific capacitance of 680 F g −1 at 1.0 A g −1, and good stability of 89.3% capacitance retention after 10000 cycles at 6.0 A g −1 . Graphical abstract: The schematic diagram of the 3D flower-like Co3 (PO)4 towards electrochemical sensing and supercapacitor applications. Image 1 Highlights: 3D Flower-like Co3 (PO4 )2 was synthesized by the facile co-precipitation method. The modified electrode exhibited broad linear ranges, low detection limits, and higher sensitivity for the electrochemical detection of RU and QCT. RU and QCT were successfully employed in real fruit samples with high selectivity. The electrochemical supercapacitor was further performed using a CPO/NF electrode that showing an excellent specific capacitance, and good stability.